Investigating cutaneous tuberculosis and nontuberculous mycobacterial infections in a Department of Dermatology, Beijing, China: a comprehensive clinicopathological analysis - Wang, Xin-Yu; Jia, Qian-Nan; Li, Jun; Zheng, He-Yi (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundCutaneous tuberculosis (CTB) and nontuberculous mycobacteria (NTM) infections present considerable diagnostic and therapeutic challenges. This study aims to provide a comprehensive clinicopathological analysis of CTB and NTM infections.MethodsWe conducted a retrospective analysis of 103 patients diagnosed with cutaneous tuberculosis (CTB) and nontuberculous mycobacteria (NTM) infections at a Beijing dermatology department from January 2000 to January 2024. Demographic, clinical, histological, and laboratory finding data were collected. Diagnostic methods and histopathological examination were recorded. Treatment regimens and outcomes were reviewed. Descriptive statistics were used to summarize demographic and clinical data, and continuous variables expressed as means and standard deviations (SD), and categorical variables as frequencies and percentages. Statistical analyses were conducted using SPSS version 25.0.ResultsThe cohort included 103 patients (40.8% males and 59.2% females), with a mean age of 51.86 years. Common clinical manifestations included nodules (97.1%), erythema (74.8%), and plaques (68.9%). Histological examination revealed hyperkeratosis (68.9%), parakeratosis (23.3%), and extensive neutrophil infiltration (95.1%) were observed. Acid fast bacteria (AFB) stains and nucleic acid tests exhibited respective positivity rates of 39.6% and 52.3%, respectively. Most patients were treated with a combination of three drugs; 77.1% of patients showed improvement, with the cure rate for CTB being 20.0%.DiscussionThis study highlights the diverse clinical and histological presentations of CTB and NTM infections, emphasizing the need for comprehensive diagnostic approaches. The variability in treatment regimens reflects the complex management of these infections.ConclusionThe implementation of advanced molecular techniques and standardized treatment protocols is imperative for enhancing diagnostic precision and therapeutic outcomes.